Human Capital as a Pillar of Economic Sustainability for Retired Professional Football Players - Andi Baso Husain; Lukman Dahlan (Bata Ilyas Journal of Accounting, 2025)
This study aims to examine the role of human capital as a pillar of economic sustainability among retired professional football players. Employing a Narrative Literature Review approach, the study synthesizes scholarly literature on human capital, financial literacy, career transition, and post-retirement economic outcomes in professional sports. The findings indicate that economic sustainability is influenced not only by athletes’ sport-specific competencies but also by their ability to develop secondary human capital, including formal education, financial literacy, entrepreneurial capabilities, and social networks. The review further identifies a human capital gap, whereby excessive investment in athletic performance is often accompanied by insufficient development of transferable competencies required for post-retirement life. Financial literacy emerges as a strategic component of human capital that enables athletes to transform temporary sporting income into sustainable economic resources. This study contributes to the literature by extending Human Capital Theory into the context of professional sport and highlighting the importance of balanced human capital development in promoting long-term economic sustainability. The findings provide practical implications for football clubs, governing bodies, educational institutions, and policymakers seeking to strengthen athlete welfare beyond their playing careers. Keywords: human capital; economic sustainability; professional football players; financial literacy; career transition.